Application of Microwave‐Assisted Technologies for the Analysis of Chlorinated Solvents in Rock Samples - Kusinski, Matthew (University of Waterloo, 2012)
It has been a direction for research of late to examine the extraction process of volatile organic compounds (VOCs) from solid matrices. Removal of VOCs from a solid matrix can be challenging due to the nature of the analyte and that of the containing media. There are established techniques that have been employed in the past; however when dealing with matrices of low permeability, the established methods are not up to task. They fail due to one or more of the following reasons: prohibitive time requirements, which can be as high as eight weeks; cost due to solvent purchasing and disposal, labor, etc.; or negative bias resulting from analyte loss, a regularly experienced issue when measuring compounds of high volatility. The need for an efficient process, both in time and cost, that can avoid the all too common analyte loss or equally as serious issue of cross contamination is great. The wide spread appearance of these compounds coupled with their harmful effects makes the need to quantify them (and remediate if necessary) a high priority. The objective of this research project was to use microwave assisted technologies in the analysis of chlorinated solvents present in rock samples. The rock samples used in this research were collected from a sampling site in Guelph, Ontario, Canada. The rock cores were from a dolostone aquifer, and as such possessed low permeability for analyte extraction while containing significant moisture internally in micropores. Through the use of microwave heating, purge-and-trap concentration, as well as cryotrap focusing, the technique allows obtaining results comparable to the established MAE-GC-μECD method without the additional cost of extraction solvent, as well as without the risk of analyte loss or sample cross-contamination from aliquot removal. Additionally, the method is more iv selective, as it allows the operator to monitor relevant ion fragments owing to the use of a mass selective detector. This selectivity is invaluable when performing extractions of environmental samples that often can be contaminated with numerous pollutants.
Keywords: Chemistry